2014
DOI: 10.4162/nrp.2014.8.5.501
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects ofRubus coreanusMiquel through inhibition of NF-κB and MAP Kinase

Abstract: BACKGROUND/OBJECTIVESRubus Coreanus Miquel (RCM), used as a traditional Korean medicine, reduces chronic inflammatory diseases such as cancer and rheumatoid arthritis. However, its mechanism has not been elucidated. In this study, we examine the anti-inflammatory effects of RCM and their possible mechanisms using RAW 264.7 cells.MATERIALS/METHODSUnripe RCM ethanol extract (UE), unripe RCM water extract (UH), ripe RCM ethanol extract (RE), and ripe RCM water extract (RH) were prepared. Inflammatory response was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 44 publications
(70 reference statements)
0
19
1
Order By: Relevance
“…Proinflammatory cytokines including IL‐1β, IL‐6, and TNF‐α play major roles in the inflammation cascades (Lee et al., 2014). Under basal condition, macrophages produced low levels of IL‐1β, TNF‐α, or IL‐6, whereas LPS could induce the expression of these cytokines.…”
Section: Resultsmentioning
confidence: 99%
“…Proinflammatory cytokines including IL‐1β, IL‐6, and TNF‐α play major roles in the inflammation cascades (Lee et al., 2014). Under basal condition, macrophages produced low levels of IL‐1β, TNF‐α, or IL‐6, whereas LPS could induce the expression of these cytokines.…”
Section: Resultsmentioning
confidence: 99%
“…We suggest the effect of adiponectin on CMKLR1 expression in vivo could be limited in the lactation period due to decreased plasma levels and gene expression of adiponectin, which may contribute to maintain chemerin signaling in mammary epithelial cells. As TNF-a has a proinflammatory effect and impairs insulin sensitivity, its role in metabolic disease is well understood [31]. In the lactating cow, TNF-a plays an important role in the immune response in mastitis and has a negative effect on milk yield [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…It is found that the administration of triterpenoid component (TFRC) (25,50 or 100 mg/kg) in R. coreanus improves the pathological characteristics including colon shortening and colonic epithelium injury, and reduces the expression of pro-inflammatory factors IL-1β, IL-6 and TNF-a protein and mRNA and macrophages infiltration into colon tissue in DSS-induced mice of acute UC, whose mechanisms might be related to down-regulations of NF-κB and p38MAPK signaling [130]. Furthermore, R. coreanus extracts (ethanol and water extracts) (400 μg/ mL) treatment obviously reduces NF-κB activation and JNK and p38 phosphorylation in LPS-induced RAW 264.7 cells [131].…”
Section: Astringent Medicinementioning
confidence: 95%
“…Attenuate NF-κB expression [127] Macrophages Inhibit NF-κB activation [129] Rubus coreanus RAW264.7 macrophages Attenuate the nuclear translocations of NF-κBp65 [130] RAW 264.7 cells Reduce NF-κB activity [131] Osthole DSS-induced colonic tissue Reduce the expression of NF-κBp65 [132] Tonifying Qi and activating blood category Tou Nong San TNBS-induced colon tissue Reduce the activation of the NF-κBp65 [134] Heat-clearing and drying dampness category…”
Section: Aom/dss-induced Colon Tissuementioning
confidence: 99%